FLEXURAL VIBRATIONS OF A DOUBLE-LAYER ELASTIC PLATE - Narzullaev Muhammad Azamat (American Journals Publishing, 2025)
Consider a plate whose neutral plane coincides with the plane x, z, and the y coordinate coincides with the direction of thickness.
Keywords: Analysis of numerical, material density, problem solving, harmonic wave, wave number, deformation, linear elasticity, isotropic material, algebraic equations, transcendental equation, Müller's method, Newton's method.